The Integral Approach to Safety - Dzulqarnain, Abu Bakar; Norazura, Ismail (Penerbit Universiti Malaysia Pahang, 2016)
There is a need to balance the reliance on a traditional OSHMS being implicitly adhered to against the human contribution factor. The aim of this qualitative study paper is to describe and discuss the existing leadership styles and approaches that are being practiced and past initiatives that have produced results in OSH performance. The snowball sampling review method of literature published between years 1997 through 2016 was applied to produce the observations and discussion. Despite the progress that is being realized, there needs to be a different approach if a sustainable performance breakthrough in OSH performance is to be achieved. The integral approach leans towards transformational leadership style and attempts to acknowledge that the subjective and objective, personal and collective factors are all equally important towards establishing wholesome and robust OSHMS. Traditional reliance on discipline and rule-based compliance needs to be tempered with an interdependent realization and awareness from the individual carrying out a task that they are ultimately responsible for their safety. Leadership and management will then need to take on the role and challenge of providing support and resources to enable the development of this self-accountable culture